Ranking Candidate Offshore Wind Power Sites Using SMART Technique: A Case Study on Türkiye - Öztürk, Samet (Springer Nature, 2025)
Offshore wind energy becomes one of the promising energy sources around the globe due to its high energy yield and reducing investment cost. Türkiye is surrounded by coasts with great wind energy potential. Although there are more than 12 GW installations of onshore wind in the country, there is not a single plant of offshore wind as of 2024 in the country. Along this line, the Turkish Ministry of Energy and Natural Resources (MENR) set a 5 GW offshore wind installation goal for 2035. There are candidate areas for offshore wind installations, however the priorities among these areas are not discussed in detail in the literature. This study utilizes Simple Multi-Attribute Rating Technique (SMART) to rank candidate suitable regions for offshore power installations for Türkiye. Eight criteria, namely wind potential, water depth, shipping density, bird migration density, port availability, closeness to relevant industry, number of touristic regions and number of electrical substations nearby are selected to rank the candidate sites. The results show that Karabiga region comes first followed by Bozcaada and Bandırma regions. Hoşköy coast has the least scores among all four candidate areas. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Keywords: Offshore Wind; SMART; Türkiye